Application of the central composite design approach for optimization of the nanosilver formula using a natural bioreductor from Camellia sinensis L. extract - Rini Dwiastuti, Phingkan Alamanda Suhendra, Sri Hartati Yuliani, Florentinus Dika Octa Riswanto (Journal of Applied Pharmaceutical Science, 2022)
In recent years, the interest in applying the nanosilver technology in the medical field has increased due to its benefit for microbial inactivation. A natural bioreductor was chosen and developed in the nanosilver formulation to minimize the toxicity effects. The content of rutin makes it possible to develop an alternative bioreductor agent using black tea (Camellia sinensis L.) leaves extract. The aim of this research was to optimize the nanosilver formula consisting of black tea leaf extract and AgNO3 with the employment of central composite design. The visible absorption wavelength and transmittance percentage were observed as dependent variables. The presence of rutin in the black tea leaves extract was proved using the thin-layer chromatography (TLC) technique. It was found that the extract concentration of 2.131% (m/v) and the AgNO3 concentration of 1.379 mM were stated as the computational recommendation resulting from the predictive model with a composite desirability value at 0.998. These optimum conditions were applied in the synthesis of six nanosilver formula replications and resulted in the percentage of a prediction relative error of absorption wavelength and transmittance which were in the ranges of 1.18%–9.18% and 2.72%–8.64%, respectively. The Relative Standard Deviation (RSD) values of absorption wavelength and transmittance were 2.81% and 2.21%, respectively. The Z-average of the nanosilver particles was 124.8 nm.
Keywords: Bioreductor, Camellia sinensis L., optimization, response surface methodology